PENGARUH SUPLEMENTASI VITAMIN E TERHADAP KADAR PROSTAGLANDIN (PGF2Α) DAN INTENSITAS NYERI HAID (DYSMENORRHEA) PRIMER PADA REMAJA PUTRI - Hutagaol, Iin Octaviana; Arifuddin, Sharvianty; Syamsudin, Saidah (Asosiasi Pendidikan Kebidanan Indonesia, 2018)
Painful menstruation (dysmenorrhoe) caused by a primary phase endometrium secretion producing excessive prostaglandin F2 alpha . The research aimed at investigating the effect of vitamin E supplementation on the prostaglandin content (PGF2α) and the primary (dysmenorrhea )intensity. This was a quasi experiment reseacrh with the pre-post test control group design The research result indicates that the average PGF2α content in the intervention group who is given the vitamin E is lower than control group who is given the vitamin E is lower than the control group who is given the placebo. The pain intensity median in the intervention group who is given the vitamin E is lower than the control group who is given the placebo. There is the effect of the vitamin E supplementation on the PGF2a and the pain intesity (dysmenorrhoe). Based on the paired T- test, the PGF2aof the intervention group is (p=0.000) and the cotrol group is (p=0,0.158) with a=0.05. Based on Wilcoxon sign test, the menstrual pain intensity of the intervention group is (p=0.000) and the control group is (p=0.480)..